Resonance Vibrations of an Elastic System Supported on a Textile Layer - Zajączkowski, Jerzy (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
The vibrations of a flexible system resting on a layer of fibres are investigated in this paper. A mathematical model of the system excited by an electromagnet supplied with an alternating current is formulated. Two resonance regions are found. In one region the frequency of the varying contact force is twice the supply electric current frequency. In the other region the frequency of vibration is equal to that of the current. At the resonances the system loses contact with the layer at the moment when the reaction force becomes equal to zero.
Keywords: nonlinear vibration; layer; fibres; electromagnet excitation